Future Prospects of 5G and 6G Networks in Libya and comparison between them - Almashat Emad Abdulhafith Almukhtar (African Journal of Advanced Pure and Applied Sciences, 2024)
We know that in Libya, all communication networks are still operating with fourth-generation networks, but it is imperative to move from the next-generation networks of the fifth-generation networks existing in several countries to the sixth-generation networks by 2029, due to its tremendous evolutionary leap in terms of speed of development and high speed that aims to achieve better performance and efficiency, faster data transfer and more efficient services than its predecessors from the current networks from 2 MHz to 1 terahertz. The use of broadband data has also increased at a very fast rate, and to keep pace with the latest future applications and the rapid development of technology, especially smart devices and machines, the system bandwidth has been widely increased, and in fifth-generation mobile phone networks, including the sixth generation, and solutions to problems in previous communication network technology have been found. This article briefly discusses the architectures of 5G and 6G networks, most notably the security associated with 5G and 6G networks and information protection, and the advantages of 5G and 6G networks as energy-efficient networks compared to previous networks, as 6G networks will provide data speeds of up to 1 Tbps and wide frequency ranges from 99 GHz to 2 THz and a bandwidth of 300 GHz, and we will also provide a comparison and also the main technological problems and areas of difference between 5G and 6G. 6G technology will also provide the needs and requirements of 3D communications, the hyper universe, and others in the future, and smart cities, and automated driving, whether in aviation, traffic, or remote control.